Comparing and Contrasting MERS, SARS-CoV, and SARS-CoV-2: Prevention, Transmission, Management, and Vaccine Development - Mohammad Oves; Mithunan Ravindran; Mohd Ahmar Rauf; Mohammad Omaish Ansari; Maryam Zahin; Arun K. Iyer; Iqbal M. I. Ismail; Meraj A. Khan; Nades Palaniyar (Pathogens, 2020)
The COVID-19 pandemic is responsible for an unprecedented disruption to the healthcare systems and economies of countries around the world. Developing novel therapeutics and a vaccine against SARS-CoV-2 requires an understanding of the similarities and differences between the various human coronaviruses with regards to their phylogenic relationships, transmission, and management. Phylogenetic analysis indicates that humans were first infected with SARS-CoV-2 in late 2019 and the virus rapidly spread from the outbreak epicenter in Wuhan, China to various parts of the world. Multiple variants of SARS-CoV-2 have now been identified in particular regions. It is apparent that MERS, SARS-CoV, and SARS-CoV-2 present with several common symptoms including fever, cough, and dyspnea in mild cases, but can also progress to pneumonia and acute respiratory distress syndrome. Understanding the molecular steps leading to SARS-CoV-2 entry into cells and the viral replication cycle can illuminate crucial targets for testing several potential therapeutics. Genomic and structural details of SARS-CoV-2 and previous attempts to generate vaccines against SARS-CoV and MERS have provided vaccine targets to manage future outbreaks more effectively. The coordinated global response against this emerging infectious disease is unique and has helped address the need for urgent therapeutics and vaccines in a remarkably short time.